2015
DOI: 10.1111/jtxs.12136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrocolloids on the Rheological Characteristics of Dough and the Quality of Bread Made From Frozen Dough

Abstract: The influence of tragacanth and salep gums on the rheological characteristics of dough and the quality of flat bread made from frozen dough was investigated.Dough was prepared with gums at two levels (0.5, 1%). Farinograph and extensograph tests were carried out on dough samples. Dough was frozen at −30C and stored at −18C. At the first and third weeks of storage, the samples were defrosted and the bread was baked. After sensory evaluation, the samples were stored for 1-5 days to conduct staling tests.The wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The reason could be attributed to the hydroxyl groups in the hydrocolloid structure, which allow more water interactions through hydrogen bonding (Rosell et al, 2001). Higher water absorption with the addition of hydrocolloids suggests that the water binding capacity of hydrocolloids is higher than protein (Gharaie et al, 2015). Moreover, the influence degree on water absorption of hydrocolloids was based upon their structure and content, the present study stated that the order was HPMC > CMC > AP > XG.…”
Section: Resultsmentioning
confidence: 76%
“…The reason could be attributed to the hydroxyl groups in the hydrocolloid structure, which allow more water interactions through hydrogen bonding (Rosell et al, 2001). Higher water absorption with the addition of hydrocolloids suggests that the water binding capacity of hydrocolloids is higher than protein (Gharaie et al, 2015). Moreover, the influence degree on water absorption of hydrocolloids was based upon their structure and content, the present study stated that the order was HPMC > CMC > AP > XG.…”
Section: Resultsmentioning
confidence: 76%
“…Increased addition of guar gum in dough rolls led to the extension of shelf life (lower firmness) at unchanged sensory properties of the rolls; however, the effect of different freezing storage time were not evaluated (Pecivová et al ., ). Similarly, Gharaie et al ., presented that hydrocolloids such as Salep and Tragacanth improved the sensory parameters of final product significantly at a 3‐week freezing storage (Gharaie, Azizi, Barzegar, & Aghagholizade, ). It seems likely that only a 3% substitution of Arabic gum itself makes an even quality in brad made from frozen dough.…”
Section: Discussionmentioning
confidence: 99%
“…A past study showed that the decrease in water loss could delay the crosslinking between starch and gluten, and delay the aging of bread, so it had a positive effect on reducing the recrystallization rate of amylopectin. 42 In the process of starch recrystallization, MLP competed with amylopectin for water molecules, which reduced the formation of recrystallization. Similarly, the R 995/1022 value decreased with the increase in MLP content when bread was stored for 7 days, and the R 995/1022 value was lowest when the MLP content was 1%, which reflected the decrease in doublehelical molecular order of starch.…”
Section: Long-range Ordered Structurementioning
confidence: 99%
“…After MLP was incorporated, A 21 and A 22 were larger than those in the control group, indicating that MLP could change the content of various water molecules and effectively reduce the loss of bound water in bread, which was consistent with previous studies. 42 Moreover, the migration of free water could be reduced, mainly because MLP polyhydroxy structure easily formed hydrogen bonds with water, which weakened the interaction between starch and water and limited the mobility of water. Therefore, a decrease in A 23 area had occurred.…”
Section: Water Migration and Water Content Water Migrationmentioning
confidence: 99%